2017
DOI: 10.1016/j.jpha.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and microbiological characterization of tinctures and microcapsules loaded with Brazilian red propolis extract

Abstract: The aim of this study was to characterize tinctures and microcapsules loaded with an ethanol extract of red propolis through chemical, physicochemical and microbiological assays in order to establish quality control tools for nutraceutical preparations of red propolis. The markers (isoflavonoids, chalcones, pterocarpans, flavones, phenolic acids, terpenes and guttiferones) present in the tinctures A and B were identified and confirmed using LC/ESI/FTMS/Orbitrap. Four compositions (A, B, C and D) were prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 29 publications
0
26
0
2
Order By: Relevance
“…The VIP analysis also showed that all compounds assume values above 0.5 and therefore are no less important. So, we can not rule out the possibility that other flavonoids not quantified in this study and the possibility of synergistic effect with other classes of compounds such as isoflavans 31 (vestitol and neovestitol), phenolic acids, and pterocarpans 83 (medicarpin), not monitored during a seasonal study 34 . The red propolis extract can be understand as a multi-constituent mixture formed by several flavonoids, aromatic, phenolic, terpenes and guttiferones with multi-targets purpose 84 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The VIP analysis also showed that all compounds assume values above 0.5 and therefore are no less important. So, we can not rule out the possibility that other flavonoids not quantified in this study and the possibility of synergistic effect with other classes of compounds such as isoflavans 31 (vestitol and neovestitol), phenolic acids, and pterocarpans 83 (medicarpin), not monitored during a seasonal study 34 . The red propolis extract can be understand as a multi-constituent mixture formed by several flavonoids, aromatic, phenolic, terpenes and guttiferones with multi-targets purpose 84 .…”
Section: Discussionmentioning
confidence: 85%
“…Our research group has been performing chromatographic profile and fingerprint studies of Brazilian red propolis. Several important flavonoids have been identified in red propolis such as liquiritigenin, pinobanksin, galangin, isoliquiritigenin, formononetin, daidzein, medicarpin, guttiferone E, guttiferone B among others 5,34 (see Table S1). Based on these fingerprint studies, some available commercially flavonoids and two laboratory isolated guttiferones were chosen to monitor the concentration of phenolic compounds present in the red propolis, thus assessing variabilities over a 1-year cycle, assessing their relationship with the climate and also variability of biological activities.…”
Section: Resultsmentioning
confidence: 99%
“…The highest amount of phenolic compounds was identified in sample B (extracts B1 and B2), while the highest flavonoid content and highest antioxidant activity were observed in sample A (extracts A1 and A2), both from the state of Alagoas. Notably, that the Brazilian red propolis produced in Alagoas is the only propolis in the country that has a certificate of origin (geographical indication) due to the scientific recognition of its differentiated chemical composition [81,82].…”
Section: Resultsmentioning
confidence: 99%
“…The particle size of inulin powder was measured using a Malvern Zen 3600 Zeta sizer instrument (Malvern Instrument, Malvern, UK). The surface structure of inulin obtained by both freeze-drying and spray-drying was analyzed using scanning electron microscopy (SEM), S-300N (Japan Hitachi, Japan) [12,14,15,24].…”
Section: Methodsmentioning
confidence: 99%